2021
DOI: 10.1016/j.isci.2021.102503
|View full text |Cite|
|
Sign up to set email alerts
|

General method to stabilize mesophilic proteins in hyperthermal water

Abstract: Summary The stability of protein structures and biological functions at normal temperature is closely linked with the universal aqueous environment of organisms. Preserving bioactivities of proteins in hyperthermia water would expand their functional capabilities beyond those in native environments. However, only a limited number of proteins derived from hyperthermophiles are thermostable at elevated temperatures. Triggered by this, here we describe a general method to stabilize mesophilic proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…P 1 M 10 can embed proteins through intermolecular forces to form a nanoformulation. We have shown that P 1 M 10 renders the embedded proteins stable at a high temperature , and maintains slow insulin release into blood for a long period of time . Here, we utilize these advantages of P 1 M 10 to improve the immune responses induced by an HIV-1 vaccine candidate.…”
mentioning
confidence: 99%
“…P 1 M 10 can embed proteins through intermolecular forces to form a nanoformulation. We have shown that P 1 M 10 renders the embedded proteins stable at a high temperature , and maintains slow insulin release into blood for a long period of time . Here, we utilize these advantages of P 1 M 10 to improve the immune responses induced by an HIV-1 vaccine candidate.…”
mentioning
confidence: 99%